2020
DOI: 10.1021/acsomega.0c02717
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a Process for Color Improvement of Low-Grade Dark Maple Syrup by Adsorption on Activated Carbon

Abstract: Low-grade dark maple syrup was successfully discolored on activated carbon. Several experimental parameters were tested, namely, the mixing time (20, 40, and 60 min), concentration of the activated carbon (0.1, 0.3, and 0.5 g/100 mL), type of activated carbon (I, II, and III), activated carbon particle size (25, 50, and 75 μm), stirring speed (200, 400, and 600 rpm), and temperature (40, 60, and 80 °C). The obtained results showed that the discoloration is optimal by applying the following parameters: a mixing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…One possible approach to achieve this goal is to use activated carbon, which has been demonstrated to be effective in reducing color precursors and off-flavors. This method has been explored in the work of Aït-Aissa et al [111] and has been shown to be effective in improving the quality of glucose syrup by removing unwanted compounds [111].…”
Section: Other Processes To Improve the Quality Of Syrupmentioning
confidence: 99%
“…One possible approach to achieve this goal is to use activated carbon, which has been demonstrated to be effective in reducing color precursors and off-flavors. This method has been explored in the work of Aït-Aissa et al [111] and has been shown to be effective in improving the quality of glucose syrup by removing unwanted compounds [111].…”
Section: Other Processes To Improve the Quality Of Syrupmentioning
confidence: 99%